Mapping the Global Research Landscape on Cyberbullying in Guidance and Counseling: A Bibliometric Analysis - Emsi Magdalena Seme; Yusi Riksa Yustiana; Syamsu Yusuf LN; Anderias Henukh (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study conducted a bibliometric analysis to map the global research landscape on cyberbullying in the context of guidance and counseling. A total of 195 scientific papers indexed by Scopus from 2015 to 2025 were analyzed quantitatively using RStudio (Bibliometrix) and VOSviewer. The analysis showed a significant increase in scientific productivity, with the United States, Spain, and Turkey as the main contributors. Most publications (78%) use quantitative methods and focus on adolescent populations (63%). The thematic evolution analysis revealed a shift in research focus from behavioral identification towards preventive interventions, detection systems, counseling, and the use of technology such as machine learning. The article by Radovic et al. (2016) received the highest number of citations (223). Developing thematic areas emphasize mental health, digital identity, and technology-based counseling strategies. The implications of this study highlight the urgency of developing adaptive, evidence-based digital counseling policies and integrating digital literacy into prevention programs. Keywords: cyberbullying, guidance and counseling, bibliometric analysis, research map, digital intervention